Exploring movement-related cortical potentials, reaction time and force production during the sprint block start of expert and novice sprinters: A case series - Botha, Marnelle (Stellenbosch : Stellenbosch University, 2023)
Thesis (MSc)--Stellenbosch University, 2023.